Desain taplak meja dan sarung bantal kursi dari limbah kain tenun sutera berbagai motif - Faizal Amir; Asiani Abu; Syamsiarna Nappu (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The partner of this Community Partnership program(PKM) was Aminah Akil Silk. The partner experiencedproblems in aspects of (1) the production of tablecloths andcushion cover seats was still very limited; (2) the quality of theproduction of tablecloths and pillowcases for chairs isclassified as poor; (3) lack of knowledge about the design oftablecloths and cushion covers for the main raw material forsilk fabrics, (4) lack of skills to make tablecloths and cushioncover for the main raw material for silk fabrics. The solutionsprovided in solving partner problems were (1) increased thequantity and quality of the production of tablecloths andpillowcases; (2) provided counseling and training on thedesign of tablecloths and pillowcases for silk fabric chairs; (3)accompanied the partner to make tablecloths and silk fabricchair cover. The methods used were demonstration, discussion,question and answer, and assistance. The results achieved were(1) the partner has the knowledge and skills to increase thequality and quality of the production of tablecloths and chaircushion cover; (2) the partner has knowledge of the materialsused to make tablecloths and chair cushion cover; (3) thepartner are skilled in making tablecloths and cushion coverchairs, ranging from choosing materials, making patterns,cutting, sewing, and tidying.